Facile synthetic method for peptoids bearing multiple azoles on side chains. Issue 1 (14th June 2022) - Lee, Yen Jea; Park, Soyeon; Kim, Yujeong; Kim, Sun Hee; Seo, Jiwon
Abstract: Natural metalloenzymes stabilize metal centers by utilizing multiple imidazole moieties. Inspired by nature's design principles, the introduction of multiple azoles into ligands has been an effective method for constructing transition metal complexes. Herein, we describe a post‐synthetic modification of peptoids to incorporate multiple azoles on side chains. A simple substitution reaction between an azole (imidazole, pyrazole, 1, 2, 3‐triazole, and tetrazole) and a chloroalkyl‐containing peptoid provided access to a variety of azole‐containing peptoids. Ten azole‐containing peptoids were synthesized from a single chloroalkyl‐containing peptoid, and the efficiency of each azole for the substitution reaction was evaluated. We have identified that several of the azole‐containing peptoids are capable of binding with Cu(II) and Fe(III). Our synthetic approach can contribute to the expansion of peptoids' chemical diversity and the development of novel peptoids for metal recognition and catalysis. Abstract :